1992
DOI: 10.1111/j.1365-2222.1992.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the linkage between chromosome 11q and atopy

Abstract: Previous work has suggested that there is a genetic predisposition for the development of both asthma and atopy. A recent study has also shown that there is a striking link between chromosome 11q and the IgE response underlying asthma and rhinitis. To further assess the linkage between chromosome 11q and atopy, we have studied nine families of two and, in many instances, three generations with the index case having asthma and/or atopy. Using two restriction fragment length polymorphism probes associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 31 publications
0
30
1
Order By: Relevance
“…Using linkage analysis, Cookson and coworkers obtained evidence for the chromosomal localization of an atopy gene on chromosome 11q13 (Cookson et al 1989) and recently Shirakawa et al (1994b) identified the subunit of the high-affinity immunoglobulin E receptor (FCER1B) as the atopy gene. Attempts to replicate this finding by linkage analysis, however, produced two positive (Collee et al 1993;Shirakawa et al 1994a) and seven negative results (Amelung et al 1992;Hizawa et al 1992;Kawakami 1992;Lympany et al 1992;Rich et al 1992;Coleman et al 1993;Brereton et al 1994). These controversial findings might in part be the result of using model-dependent methods for linkage analysis under conditions where the mode of inheritance of atopy is unknown.…”
Section: Introductionmentioning
confidence: 60%
“…Using linkage analysis, Cookson and coworkers obtained evidence for the chromosomal localization of an atopy gene on chromosome 11q13 (Cookson et al 1989) and recently Shirakawa et al (1994b) identified the subunit of the high-affinity immunoglobulin E receptor (FCER1B) as the atopy gene. Attempts to replicate this finding by linkage analysis, however, produced two positive (Collee et al 1993;Shirakawa et al 1994a) and seven negative results (Amelung et al 1992;Hizawa et al 1992;Kawakami 1992;Lympany et al 1992;Rich et al 1992;Coleman et al 1993;Brereton et al 1994). These controversial findings might in part be the result of using model-dependent methods for linkage analysis under conditions where the mode of inheritance of atopy is unknown.…”
Section: Introductionmentioning
confidence: 60%
“…Chromosome 11q13 was the first region to which a putative atopy gene was localised (Cookson et al 1989) and members of the same group later identified the β-subunit of the high-affinity IgE receptor as a candidate gene for atopic diseases (Sandford et al 1993). Other groups (Adra et al 1999;Collee et al 1993;Cox et al 1998;FolsterHolst et al 1998;Hizawa et al 1998;Shirakawa et al 1994Shirakawa et al , 1996van Herwerden et al 1995) have confirmed genetic linkage to the 11q13 region, whereas other groups have not detected linkage to atopic disease (Amelung et al 1992;Brereton et al 1994;Coleman et al 1993;Deichmann et al 1999;Hizawa et al 1992;Lympany et al 1992;Rich et al 1992). We have found only weak evidence in favour of linkage for 11q13 to raised allergenspecific serum IgE levels.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the chromosome 11q some studies have confirmed the linkage of atopy and bronchial hyperresponsiveness to markers on 11q13 (Adra et al 1999;Collée et al 1993;Daniels et al 1996;van Herwerden et al 1995;Mao et al 1997;Shirakawa et al 1994a;Young et al 1992), while others have failed to find the linkage (Amelung et al 1992; Collaborative Study on the Genetics of Asthma 1997; Hizawa et al 1992;Lympany et al 1992;Malerba et al 1999;Ober et al 1998;Rich et al 1992;Wjst et al 1999;Yokouchi et al 2000). Meanwhile, the gene for the β-chain of the high-affinity receptor for IgE (FcεRIβ) has been identified as a candidate gene for this linkage between atopy and 11q13 (Sandford et al 1993), and two coding variants in exon 6 of FcεRIβ, Ile181Leu/Ile183Val and Ile181Leu, are reported to be associated with atopy in British subjects (Shirakawa et al 1994b).…”
Section: Introductionmentioning
confidence: 93%